2006
DOI: 10.4049/jimmunol.177.7.4299
|View full text |Cite
|
Sign up to set email alerts
|

Dual Ligand Stimulation of RAW 264.7 Cells Uncovers Feedback Mechanisms That Regulate TLR-Mediated Gene Expression

Abstract: To characterize how signaling by TLR ligands can be modulated by non-TLR ligands, murine RAW 264.7 cells were treated with LPS, IFN-γ, 2-methyl-thio-ATP (2MA), PGE2, and isoproterenol (ISO). Ligands were applied individually and in combination with LPS, for 1, 2, and 4 h, and transcriptional changes were measured using customized oligo arrays. We used nonadditive transcriptional responses to dual ligands (responses that were reproducibly greater or less than the expected additive responses) as a measure of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 111 publications
4
19
0
Order By: Relevance
“…PGE 2 has been well documented to act in an autocrine manner, acting back on the producer cell to induce the secretion of nonprostaglandin factors such as matrix metalloproteinase-9 (60) and IL-6 (27), which are involved in multiple types of infection (3,37,44). Using gene chip analysis, Zhu et al have reported a number of macrophage genes that are induced after stimulation by PGE 2 (61). Only one of the induced genes (i.e., IL-1␤) is associated with downregulation of MHC class II expression, although via CIITA-mediated inhibition of class II transcription (48,61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGE 2 has been well documented to act in an autocrine manner, acting back on the producer cell to induce the secretion of nonprostaglandin factors such as matrix metalloproteinase-9 (60) and IL-6 (27), which are involved in multiple types of infection (3,37,44). Using gene chip analysis, Zhu et al have reported a number of macrophage genes that are induced after stimulation by PGE 2 (61). Only one of the induced genes (i.e., IL-1␤) is associated with downregulation of MHC class II expression, although via CIITA-mediated inhibition of class II transcription (48,61).…”
Section: Discussionmentioning
confidence: 99%
“…Using gene chip analysis, Zhu et al have reported a number of macrophage genes that are induced after stimulation by PGE 2 (61). Only one of the induced genes (i.e., IL-1␤) is associated with downregulation of MHC class II expression, although via CIITA-mediated inhibition of class II transcription (48,61). Interestingly, like the factor responsible for class II downregulation by F. tularensis infection supernatants, IL-1␤ is Ͼ10 kDa and resistant to PK treatment (25).…”
Section: Discussionmentioning
confidence: 99%
“…On a global front, the analysis of high throughput experimental data has demonstrated more detailed understanding of large scale gene expressions in innate immune system (Ricciardi-Castagnoli and Granucci, 2002;Zhu et al, 2004Zhu et al, , 2006Hirotani et al, 2005;Nilsson et al, 2006). Despite this, we are yet to have a comprehensive view of TLR signaling events due to the lack of understanding in the interplay between the dynamics of gene regulatory networks and signaling pathways.…”
Section: )mentioning
confidence: 99%
“…For instance, Ramsey et al combined mRNA expression analysis using microarrays with motif scanning of transcription factor binding sites, inferring a network of asso-ciations between transcription factor genes and clusters of co-expressed target genes (8). Similarly, transcriptome analyses revealed crosstalk between pathways downstream of TLR4 (9) and among the three transcription factors NF-B, C/EBPdelta, and ATF3 that discriminates between transient and persistent TLR4-induced signals (10).…”
mentioning
confidence: 99%